ABOUT ERRORS WHICH ARE FORMING IN STATIC PENDULUM GRAVIMETERS BECAUSE OF ZERO-POINT DRIFT AND NON-LINEAR BEHAVIOR - B. A. Blazhnov; I. Z. Gilavdary (Приборы и методы измерений, 2015)
We report here on an error analysis which has been done in relation to zero-point drift problem in gravimeters and the problem of non-linear behavior of the transfer function, while the inverse transfer function does not change. Possible effects leading to these problems and some methods of canceling the corresponding errors are considered.